FAKTOR-FAKTOR YANG MEMPENGARUHI PETANI MELAKUKAN PERUBAHAN TANAMAN KARET MENJADI TANAMAN SAWIT DI DESA PADANG SAWAH KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - M. Zaki Umaroh; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The change of rubber plant to oil palm plantation is usually called as land convertion. Land convertion is the function change of rubber plant land partial or all land area to be oil palm plantation land. This research was conducted at Padang Sawah Village Kampar Kiri District Kampar Regency. The purpose of this research is to find out the factors that cause rubber farmers change the rubber plant land to oil palm land. The research population were 78 rubber farmers that had changed their land to be oil palm land. Data collection techniques were observation, guided interview, and documentation, then the data were analyzed descriptively. This research found out that the factors which influence farmers in changing the plantation kind are economic aspect, environment aspect, and technical aspect. This research also found out that farmers’ income is influenced by how much land they process to be oil palm plantation. The land change has positive and negative impact. The positive impact is that 100% respondents answered after conducting change of plantation kind, their income increase compared to the previous job, the vacancies are opened and oil palm plant is friendly towards climate change. The negative impact is that cost of processing the oil palm is big, susceptible of environmental pollution, and the family expenses frequently increase. Keywords: Land Convertion, Economic, Environment, Technique, Environmental Pollution